2016
DOI: 10.14393/bj-v32n4a2016-32935
|View full text |Cite
|
Sign up to set email alerts
|

Substract and temperature effect on xylanase production by aspergillus fumigatus using low cost agricultural wastes

Abstract: This study reports the optimization of xylanase production under solid state fermentation (SSF) by a thermotolerant Aspergillus fumigatus strain (SCB4) isolated from sugarcane bagasse piles of Brazilian Cerrado. Different combinations of low-cost agricultural byproducts in SSF were evaluated: sugarcane bagasse and wheat bran (1:1), sugarcane bagasse and corn straw (1:1) and only sugarcane bagasse. The enzyme biosynthesis by SSF was carried out at different temperatures (40, 45, 50 and 55 o C). The maximum leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 20 publications
1
7
1
1
Order By: Relevance
“…In terms of optimal reaction pH, xylanases remained active at higher pH (pH 5) while at pH 3, their performance was reduced by 50% in comparison to the optimum conditions. These results are in agreement with those reported by Xiong who established the loss of solubility of xylanases at pH 3.5 (Xiong, Von Weymarn, Leisola, & Turunen, ) and with Gomes who reported an optimal activity at pH 4.5 and proved 60% loss of enzyme activity at pH 3 (Gomes, Santos, Fransciscon, & Baffi, ). In conclusion, pH is a crucial factor for enzyme activity and therefore it was not possible for xylanases to work at pH 3 where in turn the anthocyanins exhibited more stability.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In terms of optimal reaction pH, xylanases remained active at higher pH (pH 5) while at pH 3, their performance was reduced by 50% in comparison to the optimum conditions. These results are in agreement with those reported by Xiong who established the loss of solubility of xylanases at pH 3.5 (Xiong, Von Weymarn, Leisola, & Turunen, ) and with Gomes who reported an optimal activity at pH 4.5 and proved 60% loss of enzyme activity at pH 3 (Gomes, Santos, Fransciscon, & Baffi, ). In conclusion, pH is a crucial factor for enzyme activity and therefore it was not possible for xylanases to work at pH 3 where in turn the anthocyanins exhibited more stability.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, we found that the best temperature for the enzymatic reaction was 40 °C. Although the optimal activity reported for xylanases was at 60 °C (Gomes et al., ), obtained results indicated on anthocyanins degradation at 50 °C. Thus, to improve enzymatic activity, temperature was raised to 40 °C instead of 30 °C.…”
Section: Resultsmentioning
confidence: 96%
“…On the other hand, the xylanase produced by A. terreus NRRL260 recording 804 U. g -1 ds in the present work was better than that produced by A. terreus isolate grown on wheat bran through SSF recording 116 U. g -1 ds (Kaushik and Malik, 2016) and also better than that produced by A. fumigates strain SCB4 grown on a mixture of sugarcane bagasse and wheat bran (1:1) through SSF recording 574 U. g -1 ds (Gomes et al, 2016).…”
Section: Figcontrasting
confidence: 52%
“…Xylanase activity was the highest at 55C (Figure 3) and pH 5.0 (Figure 4). According to other studies, the optimum pH and temperature for A. fumigatus growth ranged 3.0-6.0 and 55C-60C, respectively (Ang et al, 2013;Gomes et al, 2016).…”
Section: Optimisation Of Conditions For Xylanase Productionmentioning
confidence: 80%